Effects of body contact during incremental and intermittent exercise on running power in handball players - Akashi, K.; Tanaka, M.; Tanaka, H.; Higaki, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
The purposes of this study were (1) to examine the effect of body contact (BC) on running power, and (2) to evaluate the relationship between physical ability and BC during measurement of both aerobic exercise and intermittent anaerobic running power in 14 male university handball players, all of whom were court players. Significantly shorter running distances were achieved in the yo-yo intermittent endurance test [yo-yo IE] with full BC than without BC, and there was a significant relationship between the final distance run and the degree of BC. Intermittent exercise was measured by the intermittent shuttle sprint test (ISST) that involved eight 20-m shuttle sprints with a 20-s rest period after each sprint. The subjects exhibited a significantly lower retention rate during the eighth repetition of the ISST with BC than during the eighth repetition of the ISST without BC, but there was no significant correlation between the mean retention rates during the two tests. A positive correlation between retention rates during the ISST BC and muscle strength and body weight was evident from the first 2~3 sets of the ISST with BC, and a negative correlation was evident between the retention rates during the ISST BC and the yo-yo IE from the first 5 sets of the ISST with BC. These results indicate that intermittent anaerobic running power is important for high aerobic ability. However, for intermittent exercise that includes BC, higher body weight and muscle strength are necessary to prevent any decrease in running power.